Determinandes dos rendimentos do trabalho no Brasil: uma abordagem do tipo minceriana segundo categorias ocupacionais - Monte, Marcelo Mesquita (2010)
Based upon the traditional mincerian approach for the determinants of labor income, we conduct a specification analysis for nine occupational groups in Brazil, according to PNAD 2009 database. Mincerian equations for each the categories are estimated using the Newey-West proposal and the results show that: i) the marginal impact of education on income growth differs dramatically between the occupations whose increase is, in average, 13.4%; ii) While for the group of employers and managers an additional year of study implies in a wage growth of approximately 21.2%, to landowners such increase is only 7.4%. The specification in occupational groups also identifies that discrimination by gender and race in Brazil is exacerbated in the group of rural employers and manual unskilled, respectively.